Blockchain and its Applications in Industry 4.0 - Namasudra, Suyel; Akkaya, Kemal (Singapore : Springer Nature Singapore : Imprint: Springer, 2023)
This book discusses fundamentals of Blockchain technology and Industry 4.0. It discusses many applications of Blockchain technology in Industry 4.0, including integration of AI, IoT, and big data with Blockchain for Industry 4.0. It provides cutting-edge research content from researchers, academicians, and other professionals from different background areas to show their state-of-the-art knowledge to use Blockchain in Industry 4.0. The book discusses advantages of Industry 4.0, such as improved productivity, improved efficiency, flexibility, agility, better user experience, and many more, and also entails some challenges too, such as trust, traceability, security, reliability, transparency, etc., for creating an application of Industry 4.0. The book helps graduate, postgraduate, doctoral students, and industrial professionals to implement Blockchain in Industry 4.0.
Introduction to Blockchain Technology -- Introduction to Industry 4.0 -- Blockchain in Supply Chain Management -- Government Applications and Standards to Use Blockchain -- Application of Blockchain in Mining 4.0 -- Integration of Data science and IoT with Blockchain for Industry 4.0 -- Innovations in Blockchain Technology using Artificial Intelligence -- Blockchain and Artificial Intelligence for Business Transformation towards Sustainability -- Blockchain in Big Data for Agriculture Supply Chain -- Novel Smart Homecare IoT System with Edge-AI and Blockchain.
Keywords: Computational intelligence; Artificial intelligence; Blockchains (Databases).; Medical informatics; Computational Intelligence; Artificial Intelligence; Blockchain; Health Informatics